Genetic variants in STAT3 are associated with nonalcoholic fatty liver disease - Sookoian, Silvia Cristina (2008)
Aims: To investigate the role of gene variants and derived haplotypes of the STAT3 transcription factor in nonalcoholic fatty liver disease (NAFLD) and their relation with the clinical disease severity. Patients & Methods: 108 patients with NAFLD and different stages of clinical disease severity, and a group of 55 healthy individuals were included in a Hospital-based study. We selected 3 tagSNPs showing a minor allele frequency >10 % (rs2293152 C/G, rs6503695 C/T, and rs9891119 A/C) encompassing 68.55 kb in chromosome 17, representing 24 polymorphic sites (r2 >0.8). Results: In univariate analysis, there were significant differences in the allele frequency of the rs6503695 and rs9891119 between the healthy individuals and NAFLD patients (empiric P =0.021 and 0.020, respectively). The test results for the multi-marker analysis showed that haplotypes TA and CC of tagSNPs rs6503695, rs9891119 were significantly associated with NAFLD (empiric P = 0.035 and 0.015, respectively). When we tested the hypothesis of a relation between the gene variants and the clinical and histological spectrum of NAFLD by multinomial analysis, a significant association was observed with rs9891119 (P = 0.02). Conclusions: Our study suggests a potential role of the STAT3 polymorphisms and their haplotypes in susceptibility to NAFLD and disease severity.